Race among Friends : Exploring Race at a Suburban School - Modica, Marianne (Book collections on Project MUSE., 2015)
"Race continues to be an important factor in youth identity and a stratifying element within school environments. The desire to ignore race in favor of a "colorblind" approach has so permeated America's cultural ethos that many whites, teachers included, fear that talking about race in any capacity leaves them open to accusations of racism. As a result, race has become a taboo subject in many classrooms, with serious implications for students and teachers. Race among Friends examines the varied and complex ways students and teachers think about race as they study multicultural literature in suburban high school classrooms. This book explores how African American and white students, although friends, maintained racial boundaries and felt marginalized because of their racial background, and how white teachers made instructional choices that were influenced by misperceptions or anxiety regarding the topic of race. Through in-depth analysis, Race among Friends explores cross-racial relationships among students and teachers with the goal of creating classroom environments that encourage much needed conversations about race. Teachers, administrators, and people who care about children and youth must consider the complex ways students form racial identities and the continuing influence of race on school policies and practices, even in friendly educational settings. Race among Friends recommends ways that school administrators and teachers can facilitate broader understandings among students of how race continues to affect their educational experiences and their lives"--